MANAGEMENT OF THE WORKPLACES BY THE FACILITIES OF OPERATIONS RESEARCH - Geseleva, Nataliia; Proniuk, Ganna; Romanyuk, Olexander; Akimova, Olga; Troianovska-Korobeynikova, Tetiana; Savytska, Liudmyla; Rakhmetullina, Saule; Mekebayev, Nurbapa (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2022)
The optimal location of workplaces plays an important role in the structure of occupational safety. The design of the workspace should ensure the optimal distribution of functions between person and machine in order to create safe working conditions, reduce the severity of work and the level of production injuries. Most often, workplace planning is carried out manually, by simple calculation, and then the rationality of workplace planning is evaluated, based on statistics of industrial accidents and occupational diseases, as well as indicators of labor productivity, for example, the ratio of compliance with norms. To solve the problem of optimal placement in the work mathematical models are built that can take into account various regulatory restrictions and are simple for further software implementation. It is proposed to choose the theory of φ-functions as a basis, which can be characterized as measures of proximity of objects. Thus, the set task of optimal placement of workplaces is reduced to the task of mathematical programming. The objective function determines the criterion of optimality – the minimization of the area or perimeter that will be occupied by the objects. This formulation of the problem is relevant because the use of the smallest production area, taking into account safety requirements, is an economic condition for effective production management. The constraint on the relative location of workplaces is set using φ-functions, which defines the decision domain. That, when formalizing restrictions, you can take into account all regulatory safety distances between workplaces, equipment, walls, etc. Thus, the work explores an approach that will allow automatic planning of the placement of a large number of technological objects, workplaces in accordance with occupational safety standards. Use of the software application, which can be implemented on the basis of the φ-functions apparatus, will significantly reduce the time of workplaces planning and increase its efficiency.